2007
DOI: 10.1002/mc.20311
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of MUC1 with β‐catenin modulates the Wnt target Gene cyclinD1 in H. pylori‐induced gastric cancer

Abstract: Beta-catenin can function as an oncogene when it is translocated to the nucleus, binds to T-cell factor (TCF) or lymphoid enhance factor and transactivate its target gene. The mechanism responsible for the activation of Wnt signaling pathway in the Cytotoxin-associated antigen A (CagA) Helicobacter pylori (H. pylori)-infected gastric carcinoma has not been elucidated. We hypothesize that whether interaction of MUC1 with beta-catenin modulates the Wnt signaling and its target gene cyclinD1 in CagA H. pylori-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 48 publications
0
43
0
1
Order By: Relevance
“…This study reported significant CagA-dependent upregulation of the Wnt target genes CCND1, Axin2 and the zebrafish c-myc ortholog myca. Moreover, CagA infection can lead to advanced gastric carcinoma through the upregulation of cyclin D1 [225] . It is thought that CagA promotes the phosphorylation of MUC1, which is a glycoprotein expressed on the apical borders of secretory epithelial cells, thereby facilitating its interaction with b-catenin, and the subsequent transcriptional activation of cyclin D1 [225] .…”
Section: Role Of Infections In Enhancing Wnt/b-catenin Pathway Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reported significant CagA-dependent upregulation of the Wnt target genes CCND1, Axin2 and the zebrafish c-myc ortholog myca. Moreover, CagA infection can lead to advanced gastric carcinoma through the upregulation of cyclin D1 [225] . It is thought that CagA promotes the phosphorylation of MUC1, which is a glycoprotein expressed on the apical borders of secretory epithelial cells, thereby facilitating its interaction with b-catenin, and the subsequent transcriptional activation of cyclin D1 [225] .…”
Section: Role Of Infections In Enhancing Wnt/b-catenin Pathway Signalmentioning
confidence: 99%
“…Moreover, CagA infection can lead to advanced gastric carcinoma through the upregulation of cyclin D1 [225] . It is thought that CagA promotes the phosphorylation of MUC1, which is a glycoprotein expressed on the apical borders of secretory epithelial cells, thereby facilitating its interaction with b-catenin, and the subsequent transcriptional activation of cyclin D1 [225] . In addition, gene expression profile analyzed in H. pylori-infected and uninfected patients undergoing chronic superficial gastritis showed that the E3 ubiquitin-protein ligase RNF138, which is involved in the ubiquitination and degradation of TCF/LEF, was downregulated by H. pylori [226,227] .…”
Section: Role Of Infections In Enhancing Wnt/b-catenin Pathway Signalmentioning
confidence: 99%
“…Componentes de la vía Wnt como β-catenina y GSK3β serían factores vinculantes entre cáncer e inflamación 27,28 y activadores de la transcripción de ciclina-D1 29,30 un importante regulador del ciclo celular sobreexpresado en cáncer 31 . Los resultados observados en el presente estudio: alto porcentaje de inmunomarcación a nivel de membrana plasmática/ citoplasma para MUC-1 como el mayor porcentaje de casos positivos en el grupo displasia/CIS a nivel nuclear para β-catenina y β-catenina fosforilada, citoplasmático y nuclear para ciclina-D1 y citoplasmático para GSK3β son coherentes con lo expuesto y concordantes con la literatura [42][43][44][45][46][47][48] . El caso de MUC-1 es particularmente interesante ya que su unión con H. pylori potenciaría la activación de las señales de transducción de vías que controlan el crecimiento celular 23 .…”
Section: Discussionunclassified
“…Cyclin D1 controls the speed of cell proliferation by regulating the cell cycle (Dai et al, 2012). Cyclin D1 can also be used as a downstream target gene of the Wnt/b-catenin signal transduction pathway, and may initiate the pathway in some cases (Udhayakumar et al, 2007;Zhang et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%